Electrocardiogram abnormality and Distance Covered during Six Minute Walk Test on Diabetes Mellitus Type 2 - Ni Made Elva Mayasari; Adhi Permana; Yudi Fadilah; Namira Amanda (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2020)
AbstractDiabetes Mellitus (DM) is a metabolic disease that has the characteristics of hyperglycemia that occurs due to abnormalities of insulin secretion, insulin action, or both. Macrovascular complications are often also referred to as secondary atherosclerosis due to DM, which can cause cerebral vascular disease, coronary arterial disease, and peripheral atrial disease. Diagnostic tools are needed for early detection in cardiovascular diseases which is accurate, inexpensive, comfortable, and available in almost health center. One of the diagnostic tools for early detection of cardiovascular diseases is an electrocardiogram (ECG). Six Minute Walk Test (SMWT) is a simple, objective, inexpensive, and efficient test to assess functional capacity and prognosis. This study aims to [nmem1] see whether there is a correlation between abnormalities of ECG and distance covered during SMWT in DM patients. This study was a cross-sectional study design from DM patients in the Polyclinic of the Muhammadiyah Hospital in Palembang. Forty patients with type 2 DM who fulfilled inclusion and exclusion criteria were selected using a consecutive sampling method. Twenty-seven patients have abnormal ECG, and only thirteen patients had distance covered during SMWT >300m. There is a correlation between abnormalities of ECG and distance covered during SMWT in DM patients with a significance value p = 0.011.Keywords: Diabetes Mellitus type 2, Eelectrocardiogram, Six Minute WalkingCorrespondence author: elva.maya@yahoo.com